A Model Ni–Al–Mo Superalloy Studied by Ultraviolet Pulsed-Laser-Assisted Local-Electrode Atom-Probe Tomography. (17th March 2015) - Tu, Yiyou; Plotnikov, Elizaveta Y.; Seidman, David N.
Abstract: This study investigates the effects of the charge-state ratio of evaporated ions on the accuracy of local-electrode atom-probe (LEAP) tomographic compositional and structural analyses, which employs a picosecond ultraviolet pulsed laser. Experimental results demonstrate that the charge-state ratio is a better indicator of the best atom-probe tomography (APT) experimental conditions compared with laser pulse energy. The thermal tails in the mass spectra decrease significantly, and the mass resolving power ( m /Δ m ) increases by 87.5 and 185.7% at full-width half-maximum and full-width tenth-maximum, respectively, as the laser pulse energy is increased from 5 to 30 pJ/pulse. The measured composition of this alloy depends on the charge-state ratio of the evaporated ions, and the most accurate composition is obtained when Ni 2+ /Ni + is in the range of 0.3–20. The γ (f.c.c.)/ γ '(L12 ) interface is quantitatively more diffuse when determined from the measured concentration profiles for higher laser pulse energies. Conclusions of the APT compositional and structural analyses utilizing the same suitable charge-state ratio are more comparable than those collected with the same laser pulse energy.